Interference of a speB 5′ untranslated region partial deletion with mRNA degradation in Streptococcus pyogenes. (22nd May 2017) - Chen, Z.; Mashburn‐Warren, L.; Merritt, J.; Federle, M.J.; Kreth, J.
Summary: The 5′ untranslated region (5′ UTR) of an mRNA molecule embeds important determinants that modify its stability and translation efficiency. In Streptococcus pyogenes, a strict human pathogen, a gene encoding a secreted protease ( speB ) has a large 5′ UTR with unknown functions. Here we describe that a partial deletion of the speB 5′ UTR caused a general accumulation of mRNA in the stationary phase, and that the mRNA accumulation was due to retarded mRNA degradation. The phenotype was observed in several M serotypes harboring the partial deletion of the speB 5′ UTR. The phenotype was triggered by the production of the truncated speB 5′ UTR, but not by the disruption of the intact speB 5′ UTR. RNase Y, a major endoribonuclease, was previously shown to play a central role in bulk mRNA turnover in stationary phase. However, in contrast to our expectations, we observed a weaker interaction between the truncated speB 5′ UTR and RNase Y compared with the wild‐type, which suggests that other unidentified RNA degrading components are required for the pleiotropic effects observed from the speB UTR truncation. Our study demonstrates how S. pyogenes uses distinct mRNA degradation schemes in exponential and stationary growth phases.